Changes in health related quality of life in mothers with inflammatory joint disease from year 2000 to 2020 – a comparative cross-sectional study - Hege Svean Koksvik; Ingrid Nilssen; Bente Jakobsen; Hilde Bjørngaard; Marianne Wallenius; Marianne Wallenius; Kjersti Grønning; Kjersti Grønning (Frontiers in Global Women's Health)
ObjectivesMore knowledge about health related quality of life (HRQoL) among mothers with inflammatory joint disease (IJD) is needed to understand the complex challenges for this group of patients. The overall aim of this study was to investigate changes in HRQoL among mothers with IJD from year 2000 to year 2020.MethodsThis study had a comparative cross-sectional design with two study groups 20 years apart, year 2000 (n = 77) and year 2020 (n = 197). Patients were identified from RevNatus, a Norwegian nationwide medical quality register (2020 cohort) and from a national centre for pregnancy and rheumatic disease (2000 cohort). Mothers with the diagnoses of rheumatoid arthritis, juvenile idiopathic arthritis, axial spondyloarthritis and psoriatic arthritis with children aged 0–6 were included. Data on HRQoL were self-reported and assessed by the RAND-36 (SF-36) questionnaire, along with data on educational status, number of children, months since last childbirth and eight questions on experienced motherhood limitations and experienced anxiety and distress for the children. Descriptive statistics were performed using the Mann-Whitney U-test, the Pearson chi-squared test and independent samples t-test. Multivariable linear regression were used to investigate changes and association between the RAND36 (SF-36) scores and the two study groups and possible confouders.ResultsThe 2020 cohort had significantly higher scores on bodily pain (p < 0.001), physical function (p < 0.001), and role physical (p = 0.01) scales compared to the 2000 cohort, indicating better health. There were no significant differences between the two cohorts in the mental health (MH) (p = 0.81), vitality (p = 0.09), general health (p = 0.06), social function (p = 0.83), and role emotional (p = 0.93) scales. Compared to the calculated norm scores, the 2020 cohort had significantly lower scores on all scales (p < 0.01) except on the MH scale (p = 0.37).ConclusionMothers with IJD were affected in most dimensions of RAND-36 (SF-36) both in year 2000 and year 2020. The findings emphasize the importance of understanding the intrusiveness of being a mother with IJD despite the improved medical treatment options over the last 20 years.